Comprehensive evaluation of corroded grounding electrodes considering the impulse characteristics - Wang, Xuemeng; Xiong, Lan; Zhang, Zhanlong; Dan, Yihua; Deng, Jun (Frontiers in Materials, 2023)
The grounding electrodes are buried in a harsh soil environment, which will cause corrosion. Corroded grounding electrodes directly affect the safe and stable operation of the power system. Therefore, it is particularly important to detect the corrosion degree of the grounding electrodes accurately. The existing methods have the following problems: 1. Power-frequency grounding resistance is used as a single criterion, and lack of considering the impulse characteristics, which is difficult to accurately judge the corrosion degree and could cause a potential safety hazard. 2. Lacking considering the environmental PH value, water content, salt content, and other factors of the buried soil, which is easy to lead to misjudgment of corrosion degree. To solve the problems, this paper studies a comprehensive evaluation of corroded grounding electrodes considering impulse characteristics. Based on thermal stability, impulse characteristics, and power frequency characteristics, the minimum safety diameter of grounding electrodes and the factors that affect the corrosion of the soil environment are studied. According to the relationship between each evaluation factors and corrosivity, the membership is calculated and combined with the comprehensive weight determined by the sum of the squares of deviation. The fuzzy evaluation method is adopted to obtain the corrosive evaluation matrix Y, and the corrosive index C is proposed to quantify the corrosive strength. Combined with the minimum safety diameter, the residual life range of the grounding electrodes is predicted and the corrosion degree is divided. Finally, a comprehensive corrosion evaluation algorithm considering impulse characteristics is proposed. The results show that this method not only considers the soil environmental factors but also considers the grounding characteristics of the grounding electrodes, especially the impulse characteristics. This method is more comprehensive than other evaluation methods which only consider the soil environment and can realize trenchless corrosion detection of grounding electrodes. Therefore, the contribution of this work is of great significance to the operation and maintenance of tower grounding electrodes.